The role of TIPS in the management of liver transplant candidates. Issue 8 (1st December 2017) - Unger, Lukas W; Stork, Theresa; Bucsics, Theresa; Rasoul‐Rockenschaub, Susanne; Staufer, Katharina; Trauner, Michael; Maschke, Svenja; Pawloff, Max; Soliman, Thomas; Reiberger, Thomas; Berlakovich, Gabriela A
Abstract : Background: Transjugular intrahepatic portosystemic shunt (TIPS) implantation is used for treatment of several complications in patients with liver cirrhosis. Recent studies have identified a survival benefit for patients on the waiting list after TIPS implantation, but the optimal time point for TIPS implantation prior to orthotopic liver transplantation (OLT) has not been established. Study: This study retrospectively assessed patients undergoing TIPS implantation before or after listing for OLT at the Medical University of Vienna. n  = 98 patients with TIPS on the waiting list between January 1993 and December 2013 were identified ( n  = 73 (74.5%) pre‐listing TIPS, n  = 25 (25.5%) post‐listing TIPS). A matched control group at the time of OLT without TIPS ( n  = 60) was included. Results: More patients with post‐listing TIPS (28.0%, 7/25) showed clinical improvement and went off‐list than patients with pre‐listing TIPS (8.2%, 6/73, p  = .0119). A similar proportion of patients with pre‐listing TIPS (19.2%, 14/73) and post‐listing TIPS (20.0%, 5/25) died on the OLT waiting list. Transplant surgery time was similar in patients with and without TIPS: 348(±13) vs. 337(±10) minutes ( p  = .5139). Estimated 1‐year post‐transplant survival was similar across all groups (pre‐listing TIPS: 76.2%, post‐listing TIPS: 86.0%, no TIPS: 91.2%, log‐rank p  = .1506). Conclusion: TIPS should be considered in all liver transplant candidates, since it can obviate the need for OLT and optimize bridging to OLT.